1998
DOI: 10.1002/elps.1150190607
|View full text |Cite
|
Sign up to set email alerts
|

Peptide mass fingerprint sequence coverage from differently stained proteins on two‐dimensional electrophoresis patterns by matrix assisted laser desorption/ionization‐mass spectrometry (MALDI‐MS)

Abstract: Identification of proteins separated by two-dimensional electrophoresis (2-DE) is a necessary task to overcome the purely descriptive character of 2-DE and a prerequisite to the construction of 2-DE databases in proteome projects. Matrix assisted laser desorption/ionization-mass spectrometry (MALDI-MS) has a sensitivity for peptide detection in the lower fmol range, which should be sufficient for an analysis of even weakly silver-stained protein spots by peptide mass fingerprinting. Unfortunately, proteins are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 22 publications
4
122
0
Order By: Relevance
“…Obtaining more than 50% of sequence coverage from a tryptic digest of a 2D-gel separated protein by either PMM or LC-MS/MS is difficult [47]. This was also found in our study as shown in Figure 3b, but it was also shown that relatively small proteins (0 -40 kDa) have a greater chance of obtaining sequence coverage of ϳ50% than medium to large proteins.…”
Section: Protein Sequence Coveragesupporting
confidence: 79%
See 2 more Smart Citations
“…Obtaining more than 50% of sequence coverage from a tryptic digest of a 2D-gel separated protein by either PMM or LC-MS/MS is difficult [47]. This was also found in our study as shown in Figure 3b, but it was also shown that relatively small proteins (0 -40 kDa) have a greater chance of obtaining sequence coverage of ϳ50% than medium to large proteins.…”
Section: Protein Sequence Coveragesupporting
confidence: 79%
“…In some cases, greater than 80% sequence coverage was observed. In order to increase the chance of identifying modified sites, at least 80% sequence coverage is desired [47]. Use of other proteases with different cleavage specificity in addition to trypsin is a good way of increasing sequence coverage [14,49,50].…”
Section: Protein Sequence Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…Interesting SDS-PAGE spots were excised from the stained gels, and the gel spots were sequentially destained, reduced, alkylated, and hydrolyzed, using modiWed porcine trypsin (Promega, Southhampton, UK), as previously described [34,35]. The extracted in-gel digested peptides were then identiWed via peptide mass Wngerprinting using MALDI-TOF MS, and the identiWed peptides were subsequently sequenced via MALDI-TOF/TOF tandem mass spectrometry (MS/MS) (Applied Biosystems, USA) at the Seoul National University College of Medicine, in Seoul, Korea [36]. Database searches were carried out using the search program, MASCOT, developed by Matrix Science Ltd (access is available on http:// www.matrix.science.com), and the ExPASy Molecular Biology Server at SWISS-PROT (http://www.expasy.ch).…”
Section: Maldi-tof and Maldi-tof/tof Analysismentioning
confidence: 99%
“…A tryptic digest (eg, peptide mixture) can be analyzed by matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. 14 The measured and optimized monisotopic mass data then are compared with theoretically derived peptide mass databases, generated by applying specific enzymatic cleavage rules to predicted/known protein sequences. High-throughput MAL-DI-based peptide mass fingerprinting (PMF) is accurate and sensitive.…”
Section: Two-dimensional Gel Electrophoresis (2de) and Mass Spectromementioning
confidence: 99%